The Emerging Roles and Therapeutic Potential of Extracellular Vesicles in Infertility - Zhou, Guannan; Gu, Yuanyuan; Zhou, Fangyue; Zhang, Menglei; Zhang, Ganrong; Wu, Ligang; Hua, Keqin; Ding, Jingxin (Frontiers in Endocrinology, 2021)
Infertility is becoming much more common and affects more couples. The past years witnessed the rapid development of the diagnosis and treatment upon infertility, which give numerous coupled more opportunities become parents. Extracellular vesicles are known as nano-sized membrane vesicles to play a major role in intracellular communication. In recent years, several basic and clinical studies have tried to investigate the correlation between the reproductive health/disorder and extracellular vesicles. However, the mechanism is still unclear. In this review, we reviewed the relationship between reproductive physiology and extracellular vesicles, and then collectively focused on the recent findings on the relationship between extracellular and infertility, and its consequent influence on the novel insight regarding the therapeutic strategies for infertility in the future clinical practice.